Transmission system development planning for Central-1 and Northern Regions of Lao PDR - P. Kongmany (2018)
This paper investigates the transmission system development plan of Electricite du Laos (EDL), specifically for the transmission development projects in the Central-1 and Northern regions of Lao PDR for the years 2010-2020. The power flow analysis at peak demand conditions is based on N-1 contingency criterion. The adjustment in transmission system development plan of EDL is to improve the reliability of such regional networks for the given years based on the economic justification (economic internal rate of return, EIRR). The economic justification will be accomplished to indicate the internal rate of return of each transmission system expansion project. This paper is used DIgSILENT program to calculate the power system index. The results of the studies have shown that, power losses, energy not supplied (ENS), system average interruption frequency index (SAIFI), system average interruption duration index (SAIDI), are reduced. In addition, the economic internal rate of return (EIRR) of each subproject can assist planers to make a reasonable discussion or determination to reinforcement and expansion planning. © 2008 IEEE.